Unexpected photoluminescence properties from one-dimensional molecular chains. Issue 3 (17th December 2015) - Yuan, Ye; Yao, Mingguang; Chen, Shuanglong; Liu, Shijie; Yang, Xigui; Zhang, Weiwei; Yao, Zhen; Liu, Ran; Liu, Bo; Liu, Bingbing
Abstract : Unlike bulk iodine, iodine molecular chains formed inside one dimensional (1D) nanochannels of AlPO4 -5 (AFI) single crystals show unexpected PL behavior. Abstract : Unlike bulk iodine, iodine molecular chains formed inside one dimensional (1D) nanochannels of AlPO4 -5 (AFI) single crystals show unexpected PL behavior. Thanks to its unique 1D structure, the PL exhibits obvious polarization both in excitation and emission, by changing the angle between the c -axis of the channels and the polarization direction of the incident laser. As pressure increases, the PL intensity increases obviously due to the population increase of (I2 ) n chains upon compression. In contrast, the breaking of the (I2 ) n chain at high temperature leads to the decrease of PL intensity. Our theoretical calculation further points out that the PL may arise from the intrinsic band structure of (I2 ) n chains.